REVIEW OF THREADED FASTENERS LOOSENING AND ITS EFFECTS - Mr. Kale Amol; Prof. S. M. Shaikh (International Journal of Innovations in Engineering Research and Technology, 2021)
Threaded components are the most important structural elements influencing significantly the strength and endurance of the whole structural assembly. Threaded connections are used for their ability to develop a clamping force and for the disassembly possibility that is important for maintenance. It has also been widely observed that fasteners turn loose when subjected to dynamic loads in the form of vibration. This reduces the preload force of bolt and leads to joint failure. Such failure can be catastrophic in safety critical applications. Threaded fasteners facilitate some machine parts such that they can be readily assembled or disassembled without making any damage to either of the components. This is needed for the purpose of clamping, setting up, servicing, inspection, overhauling, etc. However, under hostile vibration condition, threaded fasteners often fail to retain the tightening torque, thereby causing its loosening. History of evolution of screw fasteners dates back to few thousand years ago.